Characterization of the microbial community in ripened Pecorino Toscano cheese affected by pink discoloration. (June 2022) - Daghio, Matteo; Pini, Francesco; Espinoza-Tofalos, Anna; Conte, Giuseppe; Mari, Eleonora; Giannerini, Fabiola; Giovannetti, Luciana; Buccioni, Arianna; Franzetti, Andrea; Granchi, Lisa; Mele, Marcello; Rampazzo, Giulia; et al.
Abstract: Pink discoloration defect can cause economic losses for cheese producers due to the impossibility to sell the defected cheese, but few knowledge is currently available on the causes of this defect. To gain more insight on the causes that lead to the formation of pink discoloration in Pecorino Toscano cheese with the Protected Designation of Origin (PDO) status, the bacterial community in defected and not defected cheese was characterized by high-throughput sequencing of bacterial 16S rRNA gene. The bacterial community in the defected cheese significantly differed compared to the control. The relative abundance of the genera Acidipropionibacterium, Enterococcus, Escherichia/Shigella, Lactobacillus, Lentilactobacillus and Propionibacterium was higher in the cheese with pink discoloration defect. The concentration of short chain fatty acids and of lactic acid in cheese was measured and a shift towards the production of propionate in the cheese with pink discoloration defect was observed. Furthermore, the possible involvement of microbially produced vitamin B12 in the formation of pink discoloration was not supported by the data, since a tendency to a lower concentration of vitamin B12 was measured in the defected cheese compared to the control. Highlights: The bacterial community in sheep cheese with pink discoloration was characterized. The bacterial communities in the defected cheese and the control were different. The relative abundance of propionic bacteria was higher in the defected cheese. The role of vitamin B12 in the formation of pink discoloration was hypothesized.